1997
DOI: 10.1089/neu.1997.14.349
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mild Hypothermia on Nitric Oxide Synthesis Following Contusion Trauma in the Rat

Abstract: The exact mechanism of hypothermic cerebroprotection after traumatic brain injury (TBI) is not fully understood. The present study was conducted to investigate the effects of mild hypothermia on trauma-induced synthesis of nitric oxide (NO), which has been implicated in the pathogenesis of ischemic brain damage associated with glutamate neurotoxicity. Cerebral contusion was created in the rat parietal cortex by a weight-drop method, and extracellular concentrations of the NO end products nitrite and nitrate we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…After trauma, a very short-lasting peak of NO concentration as well as a transient rise in constitutive, i.e., eNOS and nNOS activity was described to occur in animals that underwent CCI trauma. [17][18][19][20][21] Within seconds after the insult, both NO concentration and cNOS activity decrease significantly and remain suppressed for up to 7 days. [17][18][19][20]22,23 NOS downregulation is most prominent in the tissue adjacent to the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…After trauma, a very short-lasting peak of NO concentration as well as a transient rise in constitutive, i.e., eNOS and nNOS activity was described to occur in animals that underwent CCI trauma. [17][18][19][20][21] Within seconds after the insult, both NO concentration and cNOS activity decrease significantly and remain suppressed for up to 7 days. [17][18][19][20]22,23 NOS downregulation is most prominent in the tissue adjacent to the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by Kader et al (1994) reported that mild hypothermia inhibited the activation of NOS following focal cerebral ischemia in rats. Sakamoto et al (1997) …”
mentioning
confidence: 99%
“…Sakamoto et al [393] used in vivo brain dialysis and CZE analysis of NO 2 − and NO 3 − to study the effects of mild hypothermia on trauma-induced synthesis of NO in the rat parietal cortex after traumatic brain injury. They showed a significant increase in NO end-products in samples from posttraumatic rats.…”
Section: Microdialysis and Push-pull Sampling Hpce Of No Metabolitesmentioning
confidence: 99%